The Role and Strategy of Spiritual Leadership of School Principals in Fostering the Character of Environmental Care for Elementary School Students - Junjun Junitri; Djam’an Satori; Cicih Sutarsih (Papanda Publisher, 2026)
This research aims to analyze the role and spiritual leadership strategy of school principals in fostering the character of caring for the environment of elementary school students. Based on the theory of Spiritual Leadership Fry (vision, hope/faith, altruistic love), this study uses a qualitative approach with a case study method at SDN Ekologi Kahuripan Padjajaran, Purwakarta. Data was collected through in-depth interviews with principals, teachers, and supervisors; participatory observation of learning activities and environmental programs; as well as documentation studies on school policies, programs, and archives. Data analysis is carried out through reduction, presentation, and conclusion drawn, with triangulation of sources, methods, and time to ensure validity. The results of the study show that the spiritual leadership of school principals plays a central role through three main functions: as a role model that displays examples of ecological behavior; as a decision maker who formulates ecological vision, waste sorting policies, cleanliness pickets, and the integration of environmental themes in the curriculum; as well as as a facilitator who provides environmentally friendly facilities such as waste banks, classroom gardens, compost areas, and recycling corners. The strategies used include the integration of environmental education in intracurricular, strengthening extracurricular and co-curricular activities based on experience, and developing a green school culture based on spiritual values. The findings show an improvement in students' ecological behaviors, including the habits of maintaining cleanliness, caring for plants, saving energy, and actively participating in environmental programs. This research confirms that spiritual leadership is an effective transformative approach to integrating spiritual values and environmental education in a sustainable manner in primary schools.